Phylogeny of influenza A(H1)pdm09 viruses, detected in Portugal between 2009 and 2016 - Pechirra, Pedro (2016)
Background: Influenza A(H1)pdm09 viruses show a constant antigenic pattern since its emergence in the 2009 pandemics. However, since then, these viruses have been increasing their genetic diversity. This fact supports the need for continuous monitoring of genetic characteristics of influenza A(H1)pdm09 viruses, which can suddenly acquire new antigenic properties or decrease their susceptibility to antiviral drugs. Methods: From the 2009 pandemic until 2016, the Portuguese NIC has detected 1634 influenza A(H1)pdm09 viruses in the scope of the Portuguese Influenza Surveillance Programme. During this period, 586 viruses were isolated and characterised antigenically by HI assays. Genetic characterisation was also performed for 195 viruses by HA1 subunit sequencing. Results: All studied influenza A(H1)pdm09 viruses revealed no antigenic diversity, being antigenically similar to the vaccine strain A/California/7/2009. In the pandemic season viruses belonged to a single genetic group 1 (A/Hong Kong/2212/2010). In the 2010/2011 season, Portuguese pandemic viruses showed some genetic diversity, being distributed by 4 genetic groups (3,4,5, and 6). During these 2 seasons, viruses presented one or two amino acid changes in antigenic sites, comparing to A/California/7/2009 vaccine strain. During 2011-2013, were detected H1 virus from group 7 (A/St. Petersburg/100/2011). Most influenza H1pdm viruses circulating in 2012/2013 belonged to the subgroup 6C (represented by A/Estonia/76677/2013) harbouring 2 amino acid substitutions in antigenic sites of hemagglutinin (S185T and S203T). Since 2013/2014 season, all H1pdm viruses clustered in the subgroup 6B (A/South Africa/3626/2013) and their hemagglutinins fixed 3 amino acid changes located in antigenic sites (K163Q, S185T and S203T). During the last season 2015/2016, within 6B group, new H1pdm viruses have emerged giving rise to a new subgroup represented by the strain A/New York/61/2015 (6B.1). Most 2015/2016 viruses present an additional amino acid substitution in HA antigenic sites comparing with the vaccine strain: S71P in 6B group and S162N in 6B.1 subgroup. Conclusions: Most influenza A(H1)pdm09 viruses, since its emergence until today, remain antigenically similar to the H1 vaccine strain - A/California/7/2009. However, over the last 7 seasons, these viruses have diversified into different genetic groups. As expected, is also observed the fixation of an increasing number of amino acid substitutions in antigenic sites. The genetic characterisation, in the scope of virological surveillance of influenza, is crucial to understand possible pathways of evolution and antigenic drift of these viruses.